Testicular Torsion due to Epididymo-orchitis in an Adolescent: A Case Report - Fakhri, Muhammad; Hasbi, Berry Erida (Department of Urology, Faculty of Medicine, Universitas Brawijaya, 2025)
Introduction. Acute scrotum in children requires rapid and accurate evaluation due to the time dependency of certain potentially dangerous conditions, such as testicular torsion. Prompt diagnosis and intervention are crucial, as delayed treatment can result in significant morbidity. In our case, the patient presented with severe pain in the left testis that occurred suddenly, with a history of pain and swelling in the left testis accompanied by fever 2 weeks prior. After examinations, it was decided to perform scrotal exploration, revealing a necrotic left testis, leading to an orchiectomy. Case. A 16-year-old boy presented with sudden left testicular pain that radiates to the left abdomen. He reported experiencing pain accompanied by fever two weeks prior, which had resolved after treatment at a community health center. Physical examination revealed that the left testis was hard and tender with severe pain on the left side of the scrotum, which was positioned higher than the right side, along with the absence of the cremasteric reflex. Laboratory results showed elevated leukocyte counts, and ultrasound imaging revealed hypoechoic areas. The patient was diagnosed with testicular torsion, and scrotal exploration was performed, revealing a necrotic testis with 360-degree rotation of the spermatic cord. Left orchiectomy and right orchidopexy were subsequently performed. Conclusion. The diagnosis of testicular torsion must be established promptly based on detailed history, physical examination, and supporting modalities such as ultrasonography. Early diagnosis is essential for initiating appropriate management, which can prevent testicular loss and other serious complications.